Content Analysis: Sustainability Report At Pt Unilever Indonesia Tbk - Yolanda Dhamayanti; Nurika Restuningdiah; Sunaryanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Stakeholder needs for information on company performance develop in line with changes and business progress. One of the developments that occur is the company's obligation to disclose social and environmental performance accountability reports or called sustainability reporting. Reporting is a means for companies to fulfill their responsibilities to society and the environment. The purpose of this study is to find out how the sustainability report at PT Unilever Indonesia Tbk for the period 2019-2021 by looking at 3 aspects of the sustainability report. The results of the study indicate that the existence of a sustainability report can advance the company in various aspects for each year. In this discussion the author uses the method of content analysis, which is used to conclude by using the technique of finding the characteristics of the message and is carried out objectively and systematically.